Growth and storage study of streptococcus agalactiae as a potential target in whole-cell based ‘systematic evolution of ligands by exponential enrichment (SELEX)’ procedure - Tan, Pei Qin; ZiXuen Gan; Helmi Wasoh; Nur Adeela Yasid; Mohd Yunus Abd Shukor; Murni Halim; Mohd Termizi Yusof; Amalia Mohd Hashim; Jaafar Abdullah; Yanty Noorzianna Manaf (hibiscus publisher, 2023)
Streptococcus agalactiae is a pathobiont that causes severe invasive infections, especially in fishponds or freshwater aquatic organisms. Streptococcus outbreak in cultured fishponds causes a negative impact on the production of fishes, especially tilapias. Therefore, it is essential to develop a reliable method for on-site monitoring of S. agalactiae in fishponds. This study aims to investigate a local S. agalactiae strain TP540K as a potential target for DNA aptamer in a whole-cell based ‘systematic evolution of ligands by exponential enrichment (SELEX)’ procedure. Before this procedure, the bacterial growth profile of S. agalactiae strain TP540K was studied. Besides, the viability of S. agalactiae strain TP540K was compared between different storage solutions (glycerol, phosphate buffer saline, distilled water) and temperatures (-20, 4 and 27 °C). In this study, S. agalactiae strain TP540K entered the log phase at 1.5 h of incubation time, thus the cells were collected at 2 h of incubation time with an OD600 value of 0.436 to proceed to SELEX process. Moreover, glycerol stock (20%, -20 °C) was the best storage condition for preservation of S. agalactiae strain TP540K until Day 84 with a cell viability of 2.48 x 107 CFU/mL. With the findings obtained, S. agalactiae strain TP540K could be utilised as a target for future study in DNA aptamer development through whole-cell based SELEX procedure, which could be useful for future investigations to overcome Streptococcus outbreak in the Malaysian aquaculture industry.